Peningkatan Hasil Belajar Melalui Model Problem Based Learning Kelas V Di Sekolah Dasar SDN 004 Sungai Besar - Rusdial Marta; Sumianto Sumianto; Nurhaswinda Nurhaswinda; Aria Heldayani (Journal on Education, 2025)
This study aims to explore the impact of the implementation of the Problem-Based Learning (PBL) model on improving the learning outcomes of fifth-grade students at SDN 004 Sungai Besar. The research employs a Classroom Action Research (CAR) approach, which was conducted in two cycles. Each cycle consisted of planning, implementation, observation, and reflection. Data was collected through observations, learning outcome tests, and field notes, and analyzed descriptively. The results indicate that the implementation of the PBL model successfully improved students' learning outcomes, with the average student score increasing from 65.4 in the first cycle to 80.2 in the second cycle. This improvement shows that PBL can enhance students' understanding of the subject matter as well as their critical and creative thinking skills. Furthermore, observations of group dynamics revealed improvements in collaboration and communication among students. However, challenges related to teacher training and limited learning resources still need to be addressed. This study suggests that the PBL model should be continued and expanded in its application at the elementary school level to enhance the quality of education.